2013
DOI: 10.5194/npg-20-417-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Fractal analysis of ULF electromagnetic emissions in possible association with earthquakes in China" by Ida et al. (2012)

Abstract: Abstract. Ida et al. (2012) identified anomalous decreases in the fractal dimension of the vertical (Z) component of the geomagnetic field, which they interpreted as precursors to the China earthquake of 1 September 2003. According to Ida et al. (2012), short-term earthquake prediction seems to be possible only by using electromagnetic phenomena. Here, it is shown that the decreases of the fractal dimension documented by Ida et al. (2012) are not really anomalous, but they are part of the normal geomagnetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The most commonly used methods to identify preearthquake ULF anomalies in geomagnetic field records are the so called spectral polarization ratio analysis [see, e.g., Hayakawa et al, 1996] and fractal analysis [Hayakawa et al, 1999]. Fractal anomalies preceding earthquakes have been extensively discussed and denied as precursors by Masci [2010Masci [ , 2013b and Masci and Thomas [2013a, 2013b, 2015b. Reports of precursory signatures in the spectral polarization ratio were proved invalid as well [see, e.g., Masci, 2011aMasci, , 2012aMasci, , 2012cMasci and Thomas, 2015b;Thomas et al, 2009b].…”
Section: Are Magnetic Polarization Ratio Anomalies Credible Precursormentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly used methods to identify preearthquake ULF anomalies in geomagnetic field records are the so called spectral polarization ratio analysis [see, e.g., Hayakawa et al, 1996] and fractal analysis [Hayakawa et al, 1999]. Fractal anomalies preceding earthquakes have been extensively discussed and denied as precursors by Masci [2010Masci [ , 2013b and Masci and Thomas [2013a, 2013b, 2015b. Reports of precursory signatures in the spectral polarization ratio were proved invalid as well [see, e.g., Masci, 2011aMasci, , 2012aMasci, , 2012cMasci and Thomas, 2015b;Thomas et al, 2009b].…”
Section: Are Magnetic Polarization Ratio Anomalies Credible Precursormentioning
confidence: 99%
“…What is more important, this correspondence is not expected always and everywhere. Conversely, if it is shown that there is close correspondence between alleged ULF magnetic precursors and geomagnetic indices (e.g., Kp ) [see Masci , , , , , , ; Masci and Thomas , , ], this indicates that the magnetic changes are part of global geomagnetic field changes and cannot be described as earthquake‐related signals. Therefore, the real issue is not the poor correlation that Currie and Waters [] have found between local ULF magnetic changes and geomagnetic indices but the correspondence that many papers have shown between ULF magnetic changes claimed to be precursors of earthquakes and global geomagnetic activity changes.…”
Section: The Study By Currie and Waters []mentioning
confidence: 99%
See 1 more Smart Citation
“…Many EM events, registered by different seismo-electromagnetic stations situated in different countries, can be related to the ionospheric perturbations located over seismoactive zones (Hayakawa, 1990;Liu et al, 2004;Rapoport et al, 2004), charged particles coming out of the Earth's interior (Carpinteri et al, 2012), water solutions flowing in the fracture area (Ishido and Mizutani, 1981), or various EM emission generation mechanisms (Nitsan, 1977;Vallianatos and Tzanis, 1998;Ogawa and Utada, 2000;Tzanis and Vallianatos, 2001) in hypocenters of earthquakes, so we cannot assert with confidence that the observed EM anomalies are of seismic origin (Masci, 2012a, b;Masci and Thomas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies led to a re-examination of many controversial observations of earthquake-related signals, which found that several methodologies used to identify magnetic precursors were invalid. Among these methods are magnetic polarization ratio (see Thomas et al, 2009b;Masci, 2011aMasci, , 2012a, fractal characteristics of the geomagnetic field components (see Masci, 2010Masci, , 2013aMasci and Thomas, 2013), and eigenvalues of the principal component analysis (see Masci, 2011b). Reports of ionospheric earthquake-related disturbances were also investigated (see Masci, 2012dMasci, , 2013bThomas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%